(untitled) (Raparin Journal of Humanities (RJH), 2023)
Dualism is the difference between the contradictions. Dualism is one of the prominent characteristics of Mahwi’s mystic poems. This comes from the experience and the deep outcomes of the psycho journey of this Arif within materialism to reach the truth. In the consequence of evaluating the basics of dualism and paradox of Mahwi, the reader will achieve to the practical mystic’s truth of this arif. The aim of the study is reaching the real results concern to the prove of mystic’s idea and demonstrating the highest level of mystic’s school of Mahwi and also focusing on the knowledge and his worldview of Mahwi in term of mystic’s dualism. Then, illustrating the capability and highest level of textual language of Mahwi’s poems in the dimension of art view of poetical texts in general and dualistic aesthetic in particular that he produced in his poems. The interesting point which is even a question for the researchers is that what are the prominent used dualisms in Mahwis’ poems? The used method of this research is (descriptive- analysis) which is based on the used data of the research